Representation of Well-Being / Ill-Being of the Modern Russian Family and Student Behaviour: The Phenomenon of Teachers' Reflection - O. V. Usova; N. G. Chevtaeva; A. S. Nikitina; C. Scavo (Russian State Vocational Pedagogical University, 2020)
Introduction. The relevance of this study is determined by the increasing role of the interaction of the educational organisation and the family in the process of students' education. In the current study, the relationship between the modern Russian family and teachers are considered through the prism of the concept of "social representation", which is interpreted as a subjective representation of teachers about the family of students in terms of certain attitudes towards the family. The students' demonstrated behaviour was selected as one of the factors influencing social representation of the family through its perception by teachers from the standpoint of well-being / ill-being.The aim of the present research is to consider the phenomenon of social representation of the family through its perception by teachers from the standpoint of well-being / ill-being as a reflection of the demonstrated "prosocial / deviant" form of behaviour among students in grades 7-11.Methodology and research methods. As the main research methodology, a systematic approach to the phenomenon under consideration was used, within the framework of which the relationships and the influence of the factor of perception by teachers of the family (functional / dysfunctional) and their attitude to the demonstrated behaviour of the adolescent (deviant / prosocial) were considered. The collection of empirical material was based on a comprehensive author's sociological study conducted by the authors in the period 2017-2019 in the Sverdlovsk region. A questionnaire survey, focused interviews and testing were used as the methods for collecting sociological information. The collection of primary sociological information was carried out by questionnaire survey among students in grades 7-11 and their class teachers, as well as by conducting focused interviews with teachers, who are class teachers in grades 7-11. The survey of teachers was carried out using Internet technologies (online). A secondary analysis of sociological data was conducted using mathematical statistics (in terms of correlation and analysis of variance ANOVA / VANOVA) using tools MS Excel, IBM SPSS, Statistic for Windows 5.5.Results. The authors found out the discrepancies between the social representation by teachers of the educational organisation of family perception and the transfer of teachers' ideas about the state of the family to the perception of the behaviour of adolescents 13-17 years old (as deviant or prosocial). In the course of the analysis of the obtained data, it was determined that the teachers' perception of the student's family as functional / dysfunctional is determined by their social ideas based on the attitudes of the professional group through the dominance of such signs of well-being as complete / incomplete family, parents' education, employment and their material security. It was also determined that the backbone factor of family well-being in the teachers' picture of the world is the interaction of the family and the school. The higher the levels of family interaction with the school, the more educators evaluate this family as functional. At the same time, the inconsistency of these attitudes of teachers was revealed. The models of representations by teachers of a functional, dysfunctional and semi-functional family on the basis of empirical data are described.Scientific novelty. For the first time, the authors of the present publication have analysed the state of the modern Russian family in the terms of social representation and the definition of its well-being / ill-being through the prism of perception by educators of the student and his or her inner circle. The characteristics of a functional and dysfunctional family are described based on the teachers' representations and the manifestation of deviation or prosocial behaviour in adolescents 13-17 years old.Practical significance. The authors make an attempt to take into account the errors in the perception by teachers of adolescents 13-17 years old, who exhibit deviant / prosocial behaviour, and representations of their families. Taking these errors into account makes it possible to identify "errors" in the educational work of educational organisations based on the provision of real assistance to the family and students. The essence and relevance of the correction of teachers of educational organisations when compiling a "family image" are scientifically proven (with the exception of the professional community's orientation on the dominance of the factors of well-being / ill-being). The directions of the development of the educational activities of educational organisations are determined, taking into account the erroneous perception by teachers of families and the further prevention of deviant behaviour of students aged 13-17.